Evaluation of the Effectiveness of Community-Based Mental Health Interventions for Adolescents in the Digital Age - Rahmi Sari Kasoema; Fitri Nurhayati; Suryati; Mahfuzhah Deswita Puteri (Miracle Journal Get Press, 2025)
The objective of this study was to evaluate the effectiveness of a digital community-based mental health intervention for adolescents. The Depression Anxiety Stress Scale (DASS-21) was utilised as a measure of depression, anxiety, and stress symptoms to ascertain the efficacy of the intervention. The experimental group participated in a group-based digital community intervention, while the control group received standardised services in the form of printed materials without group sessions. The data were analysed both descriptively and inferentially in order to establish the difference in scores before and after the intervention, as well as to compare the effectiveness between the experimental and control groups. The findings of this study suggest that the intervention has a substantial impact on the reduction of adolescent psychological symptoms (p = 0.001), in contrast to the negligible decrease observed in the control group (p = 0.083). This study contributes to the extant body of knowledge by highlighting the significance of incorporating technology, group interaction, and professional facilitation in fostering a supportive atmosphere that affects mental health, thereby going beyond the mere validation of earlier findings. This finding underscores the relevance of social support theory and cognitive-behavioral theory in the digital era, demonstrating the efficacy of online communities as a versatile platform for psychosocial interventions tailored to the needs of contemporary adolescents.